Apatinib-Induced Hand–Foot Skin Reaction in Chinese Patients With Liver Cancer - Xia, Hui; Zhou, Cheng; Luo, Zhaoxia; Zhang, Ping; Zhu, Liping; Gong, Zhao (Frontiers in Oncology, 2021)
Apatinib, an anti-tumor drug selectively targeting VEGFR2 (Vascular Endothelia Growth Factor Recpetor-2), has been proven effective in Chinese patients with liver cancer. Generally, treatment with apatinib achieves 16.1% of the overall objective remission rate (ORR) and 55.83% of the disease control rate (DCR) in Chinese patients with liver cancer. However, the prevalence of apatinib-induced hand-foot skin reaction (AI-HFSR) is noticeably high. The incidence of AI-HFSR is about 50.5%, of which Grades 1/2 and Grade 3 are 38.8% and 11.6%, respectively. In addition, potential molecular mechanisms underlying the development of AI-HFSR are poorly understood and urgently needed to be investigated histologically. In this review, we summarize and review the current efficacy of apatinib and the prevalence of AI-HFSR in Chinese patients with liver cancer. Besides, we postulate the potential mechanisms underlying the development of AI-HFSR and discuss the optimal clinical management for this unwanted cutaneous side effect.